O Mercosul ante os mega-acordos regionais: O tema do desenvolvimento sustentável e trabalho - Marcus Maurer de Salles; Marina Amaral Egydio de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This Discussion Paper identifies the rules on labor provided for in the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), the Regional Comprehensive Economic Partnership (RCEP) and the African Continental Free Trade Area (AfCFTA). Furthermore, the work compares the rules provided for in these mega-agreements with the rules on labor available in the agreements signed by Mercosur internally and with its external partners.
Keywords: K33; F13; F15; F53; 330; mega trade agreements; CPTPP; RCEP; labor law; Mercosur; WTO